DEVELOPMENT OF JUNIOR HIGH SCHOOL EDUCATION PROFESSION IN THE EDUCATION SERVICE OF KUTAI BARAT REGENCY - Yuwono Catur Saputro; Lambang Subagiyo; Laili Komariyah (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2020)
This study aims to examine the development of the profession of junior high school educators in the Kutai Barat District Education Office which includes (1) planning the development process, (2) implementation of the development process and (3) development results.The method used in this research is descriptive qualitative which aims to produce data with a descriptive qualitative analysis that describes the state of the professional development of junior high school educators in the West Kutai District Education Office. Data collection in this study was done by participant observation or participant observation, documentation and interviews. The results showed that the development of the profession of junior high school educators in the West Kutai District Education Office at the planning stage had considered management elements with indicators of man, money, materials, machines, methods, marketing, and minutes. At the implementation stage of the development of the profession of junior high school educators in the West Kutai District Education Office also considers management elements with indicators of man, money, material, machines, methods, marketing, and minutes, in the form of socialization, training, in house training, workshoap and MGMP . And at the evaluation stage the results of the development of the profession of junior high school educators in the West Kutai District Education Office showed that of 320junior high school educators as many as 95 people or 29.69% Group IVa and 13 people or 4.06% achieved Group IVb. Recommendations need to be held specifically for Classroom Action Research.